Neuroimaging of HIV-associated cryptococcal meningitis: comparison of magnetic resonance imaging findings in patients with and without immune reconstitution. (February 2016) - Katchanov, Juri; Branding, Gordian; Jefferys, Laura; Arastéh, Keikawus; Stocker, Hartmut; Siebert, Eberhard
To determine the frequency, imaging characteristics, neuroanatomical distribution and dynamics of magnetic resonance imaging findings in HIV-associated cryptococcal meningitis in immunocompromised patients we compared patients without antiretroviral therapy with patients undergoing immune reconstitution. Neuroimaging and clinical data of 21 consecutive patients presenting to a German HIV centre in a 10-year period between 2005 and 2014 were reviewed. We identified eight patients with magnetic resonance imaging findings related to cryptococcal disease: five patients without antiretroviral therapy and three patients receiving effective antiretroviral therapy resulting in immune reconstitution. The pattern of magnetic resonance imaging manifestations was different in the two groups. In patients not on antiretroviral therapy, pseudocysts (n = 3) and lacunar ischaemic lesions (n = 2) were detected. Contrast-enhancing focal leptomeningeal and/or parenchymal lesions were found in all patients under immune reconstitution (n = 3). Magnetic resonance imaging lesions suggestive of leptomeningitis or meningoencephalitis were detected in all patients with a recurrence of cryptococcal meningitis under immune reconstitution, which differs from the classical magnetic resonance imaging findings in patients without antiretroviral therapy. In antiretroviral therapy-treated patients with past medical history of cryptococcal meningitis, detection of contrast-enhancing focal meningeal and/or parenchymal lesions should prompt further investigations for a recurrence of cryptococcal meningitis under immune reconstitution.